Exploring the emerging technologies and trends of infectious diseases in the post-epidemic era - Huaiyan, Fan; Yuan, Qian; Zhijian, He; Long, Liu; Mei, Wang (Frontiers in Public Health, 2025)
This study focuses on the development of the infectious diseases department in the post-pandemic era. It reviews the impact, transformation needs, and challenges brought by the pandemic to this field. By discussing the application prospects of emerging technologies such as bioinformatics, artificial intelligence, and big data in epidemic analysis, pathogen research, and medical services, this article demonstrates how interdisciplinary technologies can promote the digital transformation of the infectious diseases department. Meanwhile, it analyzes the development trends of technologies in disease prevention, early diagnosis, innovative treatment methods, and vaccine development. Through case studies and empirical analysis, it reveals the effectiveness of data-driven decision-making in optimizing the management of the infectious diseases department. The research findings indicate the development direction of the infectious diseases department in the post-pandemic era and provide theoretical guidance and technical references for related research and practice.